Endothelial Protein kinase D1 is a major regulator of post-traumatic hyperinflammation - Schönfelder, Jonathan; Seibold, Tanja; Morawe, Mareen; Sroka, Robert; Schneider, Nora; Cai, Jierui; Golomejic, Josip; Schütte, Lena; Armacki, Milena; Huber-Lang, Markus; Kalbitz, Miriam; Seufferlein, Thomas; et al. (Frontiers in Immunology, 2023)
Trauma is a major cause of death worldwide. The post-traumatic immune response culminates in the release of pro-inflammatory mediators, translating in the infiltration of neutrophils (PMNs) at injury sites. The extent of this inflammation is determined by multiple factors, such as PMN adhesion to the endothelium, transendothelial migration, endothelial barrier integrity as well as PMN swarming, mass infiltration and activation. This process is initiated by secondary lipid mediators, such as leukotriene B4 (LTB4). We here provide evidence that Protein kinase D1 (PRKD1) in endothelial cells is implicated in all these processes. Endothelial PRKD1 is activated by pro-inflammatory stimuli and amplifies PMN-mediated inflammation by upregulation of cytokine and chemokines as well as adhesion molecules, such as ICAM-1, VCAM-1 and E-selectin. This induces enhanced PMN adhesion and trans-migration. PRKD1 activation also destabilizes endothelial VE-cadherin adhesion complexes and thus the endothelial barrier, fostering PMN infiltration. We even describe a yet unrecognized PRKD1-dependant mechanism to induce biosynthesis of the PMN-swarming mediator LTB4 directed via intercellular communication through small extracellular vesicles (sEVs) and enhanced CXCL8 secretion from activated endothelial cells. These endothelial sEVs transfer the LTB4 biosynthesis enzyme LTA4 hydrolase (LTA4H) to prime PMNs, while initiating biosynthesis also requires additional signals, like CXCL8. We further demonstrate the respective LTA4H-positive sEVs in the serum of polytrauma patients, peaking 12 h post injury. Therefore, PRKD1 is a key regulator in the coordinated communication of the endothelium with PMNs and a vital signaling node during post-traumatic inflammation.